ANALISIS PEMELIHARAAN MESIN PEMIPIL JAGUNG MENGGUNAKAN METODE FMEA DAN FTA PADA JASA PEMIPILAN JAGUNG DI DESA ALASBULUH WONGSOREJO - Dyah Fitri Ayu Kusniah; Asfarina Hidayah; Muhammad Yusuf (Journal of Industrial Engineering & Technology Innovation, 2026)
Corn is one of the strategic agricultural commodities in Indonesia that plays an important role in food security and regional economic development. In post-harvest processing, corn shelling machines are widely used to improve production efficiency and reduce manual labor. However, continuous machine operation during harvest seasons often causes component failures that can disrupt the production process and increase downtime. This study aims to identify failure modes, determine critical components, analyze the root causes of failures, and propose preventive maintenance improvements for a corn shelling machine at a corn shelling service business in Alasbuluh Village, Wongsorejo. The study employed Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) methods. Data were collected through direct observation, interviews, documentation, and historical machine failure records during January–February 2026. The results showed that the screen component had the highest failure risk, with Risk Priority Number (RPN) values of 378 for clogged screens and 336 for broken screen bars. The failures were mainly caused by dirty raw materials, high corn moisture content, lack of routine cleaning, excessive workload, and machine vibration. FTA results indicated that machine failures were influenced by human, machine, material, and environmental factors. Based on the findings, preventive maintenance procedures consisting of daily, weekly, and monthly maintenance activities were proposed to reduce downtime and improve machine reliability.